FENOMENA SOSIAL MASYARAKAT MINANGKABAU DALAM LIRIK LAGU CIPTAAN AGUS TAHER - Priska, Priska; Juita, Novia; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2013)
The purpose of this study is to explain the forms and causes of social phenomena in Minangkabau society in the lyrics of the song Seso Parambah Rimbo, Salamaik Pagi Minangkabau, and Anak Jalanan. And the creation of Agus Taher on the album Febian “Katiko Cinto Musti Mangalah